Chapter Construire un comté: Sinopoli (1330-1335) - Pollastri, Sylvie (Reti Medievali E-Book, 2021)
Charles I of Anjou restored the counties according to the Norman system; his successors im- proved them and let them become a space of local power inside the the Royal districts, the gi- ustizierati. At the same time some aristocratic families consolidated themselves, like the Ruffo of Calabria, lords of Sinopoli, who obtained the comital title in 1334. The paper analyses two important records: the cartulario 1 and the cartulario 17, integrating them with all the availa- ble documents. The cartulario 17 contains platea dating from 1335, which includes one or two older texts written in Greek and translated into Latin. It is at the same time an inventory and a municipal statute. The cartulario 17 is the main source for studying the creation, composition and ruling of the county of Sinopoli, not to mention the various world of the subjects to the lords, according to their status (vassallus) or their possessions as freemen (burgenses). We have also suffeudatarii and other people depending on the baron, like the raccomandati.